Pertanggungjawaban Etik Dokter dalam Melakukan Aksi Mogok Kerja di Indonesia - Rifandanu, Farel (UI Scholars Hub, 2025)
The implementation of strikes by doctors is a complex phenomenon with significant implication that give rise to ethical dilemma. Doctors have a responsibility to provide health services, so that a strike can endanger the health care system. On the other hand, doctors also have the right to fight for fair and decent working conditions. In view of these problems, this study has two (2) problem formulations, how the legal regulations regarding the actions of doctors who go on strike and how the ethical responsibilities of doctors who go on strike. This study uses a normative legal research method that analyzes law as norms, rules, principles, principles, theories, doctrines, and other literature, so that it can interpret, legal discovery, and synchronize the right to strike in labor law norms and medical ethics norms. So, to answer this question, the researcher analyzed in depth the positive legal texts (statutory regulations and codes of ethics) and norms, rules, principles, principles, theories, doctrines, and other literature related to the right to strike and professional ethical obligations. The results of the study indicate that strikes are a constitutionally valid right that has been guaranteed and protected by laws and regulations. Furthermore, in resolving this ethical dilemma, striking doctors must carefully consider the potential consequences of their actions on patient safety while simultaneously upholding their legitimate rights as workers by adhering to ethical responsibilities before, during, and after the strike. This is done to uphold the principles of labor law and medical ethics while striving for positive systemic improvements in the healthcare system.